Epidemiological Surveillance COVID 19 Risk Factors Nurses before and after Counseling at Medan Hospital (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Coronavirus Disease 2019 (COVID-19), which originated in Wuhan, China, has caused many healthcare workers to be infected. To better understand how to protect staff, it is necessary to understand the predisposing factors for healthcare workers infection and nosocomial transmission. A research tool using checklist, questionnaires risk factors healthcare workers (nurses), who worked at the forefront to fight against COVID-19 since its outbreak.The quiestionnare given to nurses includes neurological symptoms, washing hands, wearing masks, clothes, gloves and face shield and shoes from officers who are in the hospital. Of the seventy nurses in Medan Hospital who participated, the most were 30-40 years old as many as 40 (57,1%) and the most female nurses were 57 (81,4%). The were no difference in the level of understanding of nurses before and after counseling (p >0.05). Conclusion: Environmental risk factors at COVID-19 have no associated the Risk Factors before and after counseling at Medan Hospitals.